Pengembangan Model Pembelajaran RASI (Reading, Analyzing, Sharing, and Inferring) dalam Pembelajaran IPA di SMP - Vivi Darmayanti; Jekti Prihatin; Joko Waluyo (Jurnal Pembelajaran dan Pendidikan Sains, 2016)
The learning process that provide an opportunity for learners to learn independently is a reading method such as Think, Talk, Write (TTW), Reading, Questioning, and Answering (RQA). Based on the disadvantages and advantages of TTW and RQA, syntaxs can be combined then it is known as RASI (Reading, Analyzing, Sharing and Inferring). The purpose of this research is to produce RASI learning model with valid criteria based on Borg and Gall development model. The preliminary field testing was conducted at the State Junior High School 4 Jember. RASI learning model is validated by lectures and teachers on March 2016. The data are analyzed by analysis of percentage. The result showed that validation of RASI is 88.61% with very valid criteria. Average of teacher response 81,67% and average of students response is 83,01% with very good critera. RASI learning model is valid and it can be used in main field testing.